EXPLORING THE EFFECTS OF BRAND EXPERIENCE AND BRAND TRUST ON BRAND LOYALTY: THE MEDIATING ROLE OF BRAND LOVE - Aimi Nadia Ibrahim; Noor Hasmini Abd Ghani, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
In today’s competitive and emotionally driven markets, fostering brand loyalty requires more than just functional value. It demands meaningful consumer-brand relationships. This conceptual paper investigates the interconnected effects of brand experience and brand trust on brand loyalty, emphasizing the mediating role of brand love. Drawing from recent advancements in brand relationship literature, this study posits that positive experiences and strong trust toward a brand encourage emotional attachment development, subsequently enhancing loyalty outcomes. Current research highlights the increasing relevance of brand love in strengthening consumer commitment, especially as consumers seek more personalized and emotionally fulfilling interactions with brands. The paper synthesizes insights from recent empirical findings to propose a framework that captures the pivotal role of brand love in translating brand perceptions into enduring loyalty. This conceptual model offers valuable implications for brand managers aiming to cultivate emotional engagement and trust, fostering long-term brand loyalty. Future empirical studies are encouraged to validate this framework across varied market contexts.